Opportunities of Ionic Liquids for Lignin Utilization from Biorefinery. Issue 27 (20th July 2018) - Zhu, Xinyun; Peng, Chang; Chen, Huaxin; Chen, Qin; Zhao, Zongbao Kent; Zheng, Qiang; Xie, Haibo
Abstract: The development of economically viable biorefineries for the transformation of lignocellulose into sustainable biofuels, chemicals and materials requires effective valorization of lignin. The high solubility of lignocelluloses and lignin in ionic liquids has created new probabilities, which renders the essential significance of understanding the cell structure of biomass, isolation of lignin from biomass (IL‐lignin), elucidation of the chemical structure of wood and lignin, and valorization of IL‐lignin. In this review, we first give an overview of lignin chemistry, and then describe the current development of structural elucidation of lignin with IL‐mediations, extraction fractionation and its catalytic conversion. This review also highlight the relationship between the research challenges, lignin utilization and the properties of ILs, on which a brief conclusion and perspectives are drawn. Abstract : The high solubility of lignocelluloses and lignin in ionic liquids has created new probabilities to the value‐added utilization of lignin. In this review, we give an overview of chemistry and the current development of structural elucidation of lignin with IL‐mediations, extraction fractionation and its catalytic conversion. This review also highlight the relationship between the research challenges, lignin utilization and the properties of ILs, on which a brief conclusion and perspectives are drawn.